Strategi Marketing Politik Kang Erwin Calon Walikota Bandung 2024 dalam Penyebaran Pamflet - Yoshy Hendra Hardiyan Syah; Ahmad Ali Nurdin (Jurnal Studi Ilmu Sosial dan Politik, 2023)
Purpose: The purpose of writing this article is First, to find out the "Branding, Positioning and Segmenting" strategy used by the Bandung City PKB team in marketing Kang Erwin via Instagram in the 2024 Election. Second, to find out the response of Bandung residents in the field to the pamphlets distributed by Kang Erwin via Instagram during the momentum of Ramadhan 1444 H Methodology/approach: This article uses a qualitative descriptive analysis research method using primary data collection techniques, namely virtual observation, interviews, and documentation with a virtual ethnographic approach that is non-participatory in nature, while secondary data is in the form of books, scientific articles, theses which are still relevant in this study. The virtual observation technique used is observation on the PKB Bandung City Instagram media. Regarding the interview, the resource person in this article is Kang Erwin as the Candidate for Mayor of Bandung 2024, the informant in this article is a resident of the city of Bandung, and the interview technique used is a semi-structural interview, while the interviews were conducted on 8-10 June 2023. Subjects in This research is Kang Erwin and the object of this research is the Instagram media platform as a marketing strategy tool. Results/findings: The findings in this article are First, Branding Strategy. During the momentum of Ramadhan 1444 H, Kang Erwin through his Instagram account @pkb_bandung actively distributed campaign pamphlets with Ramadan nuances, the "branding" that was characteristic of Kang Erwin was that he always used the same personal photo, used Islamic attributes (white Muslim dress, wearing a turban , and black cap). Second, Positioning Strategy. Kang Erwin as Candidate for Mayor of Bandung 2024 uses Sundanese in the slogan used is "PKB Kahiji, Bandung Ngahiji" and PKB reflects political parties that are both religious and nationalist. Third, Segmenting Strategy. kang Erwin Candidate for Mayor of Bandung 2024 seeks to provide benefits to various levels of society, seeks to restore the dignity of the City of Bandung, namely Paris Van Java, a city of flowers, a city that is safe, peaceful, and conducive, fixing poverty by strengthening the micro-economy, and providing ambulance facilities on an ongoing basis free to the people of Bandung who need it. Then based on research conducted using field interviews on the response of Bandung city residents regarding the distribution of the Ramadhan 1444 H pamphlet by Kang Erwin on the Instagram social media @pkb_bandung that, the response of Bandung city residents was less than one million, because dominant Bandung city residents considered the campaign                         in the holy month of Ramadan 1444 H is unethical and considered to have tarnished the sacred month of Ramadan as a momentum to increase taqwa, get closer, and ask forgiveness from Allah, not for political momentum, so that Ramadan will be according to its nature.